The Emergence of the First Post-November System of Hungarian Political Parties in Slovakia - Zuzana Mészárosová-Lampl (Studia Politica Slovaca, 2022)
The so-called post-November system of Hungarian parties in what was then Czechoslovakia was established after the change in the political system in November 1989 and in the first months of 1990. It consisted of three political entities: Independent Hungarian Initiative, Hungarian Christian Democratic Movement, and the movement Coexistence. Although they distanced themselves from using the word “party” in their name, they truly were political parties that ran for parliamentary representation in the first free elections in June 1990 at the time representing the Hungarian community of more than 500 000 members in Slovakia. In her study, the author describes many hitherto unknown circumstances of the origin of these parties. In addition to contemporary documents, media appearances and other sources, the study also relies on commemorative interviews with party representatives.